Kebijakan Publik dan Kebijakan Sosial dalam Ilmu Politik - Alya Habibah Tarigan; Muliana; Khoirul Huda (Indo Publishing, 2025)
This paper discusses the relationship between public policy and social policy within the context of political science, aiming to provide a deeper understanding of their concepts, scope, and relevance to social development. Public policy is defined as a series of governmental decisions and actions designed to address social, economic, and political issues, while social policy focuses on fulfilling basic human needs and improving citizens’ welfare. Both are closely interrelated in realizing a system of governance that is just, responsive, and people-oriented. This study employs a descriptive-qualitative approach by reviewing various theories and perspectives from scholars such as Thomas R. Dye, William N. Dunn, and John Rawls, and examines their relevance to the Indonesian context, which is grounded in Pancasila and the 1945 Constitution. The findings indicate that the effectiveness of public and social policies greatly depends on community participation, bureaucratic capacity, and adaptability to global changes. Therefore, strengthening inclusive and participatory public and social policies is essential to achieving social justice and collective welfare.